Impact of primary health care on child morbidity and mortality in rural Ghana: The Gomoa experience - Afari, E.A.; Nkrumah, F.K.; Nakana, T.; Sakatoku, H.; Hori, H.; Binka, F. (Central African Journal of Medicine, 1995)
The impact of a combination of PHC intervention activities on child survival, growth, morbidity and mortality was assessed in three selected rural communities (Gomoa Fetteh, Gomoa Onyadze/Otsew Jukwa and Gomoa Mprumem) in the Central Region of Ghana from 1987 to 1990. EPI, provision of basic essential drugs and supplies for the treatment of common childhood diseases, treatment of the sick child, growth monitoring, health education, provision of antenatal services, family planning, training and supervision of Community Health Workers, disease surveillance and special studies were the major PHC strategies used to improve the health of the child and the pregnant woman in the three communities. These activities in their totality have had significant impact on morbidity and mortality in children under five and on maternal mortality in children under five and on maternal mortality over the study period 1987 to 1990. Although malaria, acute respiratory infections and diarrhoea diseases continue to be major causes of childhood morbidity, deaths due to these diseases have dramatically declined. Measles and other vaccine preventable diseases no longer contribute significantly to childhood morbidity and mortality. Infant and under five mortality have been reduced from 114.6/1000 and 155.6/1000 live births to 40.8/1000 and 61.2/1000 live births respectively. The crude birth rates however, remain almost the same over the five year period (43 to 48/1000 pop.) but crude death rates have declined (11 to 12.4/1000 pop.).(ABSTRACT TRUNCATED AT 250 WORDS)